2023
DOI: 10.1265/ehpm.22-00243
|View full text |Cite
|
Sign up to set email alerts
|

Academic-related factors and daily lifestyle habits associated with adolescent idiopathic scoliosis: a case-control study

Abstract: Background: Adolescent idiopathic scoliosis (AIS) is the most prevalent spinal deformity, which may have long-term negative consequences on adolescents. The research on the etiology is of great importance for identifying high-risk population and formulate tailored prevention. This study aimed to evaluate the association between academic-related factors and daily lifestyle habits and AIS. Methods: In this population-based case-control study, 491 AIS cases and 1,346 healthy controls that frequency-matched by age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The results of this study showed that the prevalence of anisometropia in children with scoliosis screening positive was 4.08 times higher than that in children without scoliosis (OR: 4.08, 95% CI: 3.14–5.30, p < 0.001). Spinal scoliosis inevitably leads to poor reading and writing posture ( 26 , 27 ). Pärssinen et al ( 48 ) found that in school-aged children, the trend of myopia progression was closely related to steeper reading angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that the prevalence of anisometropia in children with scoliosis screening positive was 4.08 times higher than that in children without scoliosis (OR: 4.08, 95% CI: 3.14–5.30, p < 0.001). Spinal scoliosis inevitably leads to poor reading and writing posture ( 26 , 27 ). Pärssinen et al ( 48 ) found that in school-aged children, the trend of myopia progression was closely related to steeper reading angle.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some regions in China have included scoliosis screening in students’ routine physical examinations. Considering that it has been confirmed that scoliosis is associated with poor reading and writing posture ( 26 , 27 ), and that poor reading and writing posture may cause anisometropia ( 28 ), we also included scoliosis in the study of anisometropia.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, more than 2 h of ST on weekdays was linked with adolescent idiopathic scoliosis (AIS). The same was true for low dairy product consumption [72], which, in turn, has been linked with excessive ST [37,39]. Additionally, Tremblay MS et al suggested that less than 2 h of daily ST is associated with better bone health [20].…”
Section: Musculoskeletal Systemmentioning
confidence: 98%
“…Refractive errors are the most common cause of vision impairment worldwide [ 10 ]. It has been confirmed that refractive errors are associated with poor reading and writing postures [ 11 ], and that poor reading and writing postures may accelerate the progression of scoliosis [ 12 , 13 ]. Refractive errors include myopia, hyperopia, astigmatism, and anisometropia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%